Zingiber zerumbet (L.) Smith : a review of its ethnomedicinal, chemical and pharmacological uses. - Zakaria, Zainul Amiruddin; Yob, Noor Jannah; Mohd Jofrry, Suhaidah; Meor Mohd Affandi, Meor Mohd Redzuan; Teh, Lay Kek; Salleh, Mohd Zaki (Hindawi Publishing Corporation, 2011)
Zingiber zerumbet Sm., locally known to the Malay as Lempoyang, is a perennial herb found in many tropical countries, including Malaysia. The rhizomes of Z. zerumbet, particularly, have been regularly used as food flavouring and appetizer in various Malays' cuisines while the rhizomes extracts have been used in Malay traditional medicine to treat various types of ailments (e.g., inflammatory- and pain-mediated diseases, worm infestation and diarrhea). Research carried out using different in vitro and in vivo assays of biological evaluation support most of these claims. The active pharmacological component of Z. zerumbet rhizomes most widely studied is zerumbone. This paper presents the botany, traditional uses, chemistry, and pharmacology of this medicinal plant.